A highly efficient and environmentally friendly approach for in-situ utilization of CO2 from coal to ethylene glycol plant. (1st October 2022) - Chu, Genyun; Fan, Yingjie; Zhang, Dawei; Gao, Minglin; Yu, Jianhua; Xie, Jianhui; Yang, Qingchun
Abstract: The development of carbon neutrality technology for the coal-based chemical industry is of great interest to many coal-rich countries. An improved coal to ethylene glycol process integrated with CO2 utilization for direct synthesis of dimethyl carbonate (CTEG-CU) is proposed for in-situ utilization of CO2 from the conventional coal to ethylene glycol plant to co-produce ethylene glycol and dimethyl carbonate. In the improved process, the CO2 emitted from the conventional process is reused in the dimethyl carbonate direct synthesis unit with dehydration reactive distillation. It is coincidental that the products produced by this unit are the same as the conventional process. The improved process is firstly modeled and simulated to establish its material and exergy balance models. Its techno-economic and environmental performance are compared with those of the conventional process. Results show that the carbon utilization efficiency, exergy efficiency, and internal rate of return of the improved process are increased by 58.55%, 39.23%, and 22.32%, respectively. In addition, the improved process has better environmental performance since its direct CO2 emission is significantly reduced by 96.92%. Graphical abstract: Image 1 Highlights: An improved CTEG-CU process is developed for in-situ utilization of CO2 emissions. Effect of the key operational parameters on the system performance is optimized. Carbon efficiency and IRR of the improved process are increased by 58.55% and 22.32%. Direct CO2 emission of the improved process is significantly reduced by 96.92%.